Tusk and transformation in southern African San rock art: an iconographic analysis of WAR2. Issue 3 (3rd July 2018) - Blundell, Geoffrey; Ferreira, Angela
ABSTRACT: Researchers have made significant progress in understanding the symbolism of certain animal images in southern African San rock art. What is less well understood is the combination of specific animal body parts to create composite creatures. Identifying the species from which a particular body part is taken allows for further insight and nuance in the current interpretation of San iconography. This paper explores this possibility in relation to images from the WAR2 site in the Drakensberg Mountains of southeastern South Africa. Numerous images at the site are illustrated with tusks. While the paper argues that the tusks at this site are modelled on only one species, the behavioural contexts of tusks are similar for all animals that have them in southern Africa. Linking these contexts and the natural properties of tusks to San ethnography allows for the elucidation of the imagery at WAR2.